VAV1 and BAFF, via NFκB pathway, are genetic risk factors for myasthenia gravis. (11th April 2014) - Avidan, Nili; Le Panse, Rozen; Harbo, Hanne F.; Bernasconi, Pia; Poulas, Konstantinos; Ginzburg, Elizabeta; Cavalcante, Paola; Colleoni, Lara; Baggi, Fulvio; Antozzi, Carlo; Truffault, Frédérique; Horn‐Saban, Shirley; et al.
Abstract Objective To identify novel genetic loci that predispose to early‐onset myasthenia gravis (EOMG) applying a two‐stage association study, exploration, and replication strategy. Methods Thirty‐four loci and one confirmation loci, human leukocyte antigen (HLA)‐DRA, were selected as candidate genes by team members of groups involved in different research aspects of MG. In the exploration step, these candidate genes were genotyped in 384 EOMG and 384 matched controls and significant difference in allele frequency were found in eight genes. In the replication step, eight candidate genes and one confirmation loci were genotyped in 1177 EOMG patients and 814 controls, from nine European centres. Results Allele frequency differences were found in four novel loci: CD86, AKAP12, VAV1, B‐cell activating factor (BAFF), and tumor necrosis factor‐alpha (TNF‐α), and these differences were consistent in all nine cohorts. Haplotype trend test supported the differences in allele frequencies between cases and controls. In addition, allele frequency difference in female versus male patients at HLA‐DRA and TNF‐α loci were observed. Interpretation The genetic associations to EOMG outside the HLA complex are novel and of interest as VAV1 is a key signal transducer essential for T‐ and B‐cell activation, and BAFF is a cytokine that plays important roles in the proliferation and differentiation of B‐cells. Moreover, we noted striking epistasis between the predisposing VAV1 and BAFF haplotypes; they conferred a greater risk in combination than alone. These, and CD86, share the same signaling pathway, namely nuclear factor‐kappaB (NFκB), thus implicating dysregulation of proinflammatory signaling in predisposition to EOMG.